Juridical Review of Delayed Share Acquisition Notification Damaging PT. Sinar Mitra Compensated by PT. Orix - Pakpahan, Elvira Fitriyani; Tanjaya, Willy; Azharuddin, Azharuddin; Affendy, Albert Ben (JURNAL AKTA, 2024)
The purpose of this examination is to determine the principle of legal remedies for the decision of the Business Competition Supervisory Commission (KPPU) through a follow-up examination based on the Law on Refusal Procedures. This research case study uses the principle of justice in legal efforts to challenge the KPPU's decision. The data analysis method used in this study is a normative legal analysis method that compares norms. The normative legal method is used to explain the data that defines the legal norms contained in the legislation. The results of the data analysis of this study indicate the neglect of the principle of justice in judicial efforts against the KPPU's decision. In carrying out the burden of proof, if the parties are unable to provide actual evidence, it can cause inconsistency, but if the judge determines that it is not clear, the KPPU will provide evidence through additional examination of the judge's order. added and integrated. As a result, the resistance applicant was unable to strengthen his defense because he could not provide new evidence that could acquit the applicant.